The world outlook formation of autobiographical hero in Gorky's story "My Universities" - Kondurina, E. (Literatūra, 1970)
The well-known Gorky's story "My Universities" is not enough studied as an independent work. The existing literature about this story as a rule researches the typical traits of autobiographical hero's character and does not turn its attention to the logic of his vital impressions and hesitations, to the connection of emotional and rational.This aspect of content presents a great interest insofar as Gorky gives the original model of formation of the scientific world outlook of common man, that does not lose its importance today.Gorky in his story shows the process of the formation of hero's views to the world dependent from his emotional life. The study of this connection permits to see how many mistakes the investigators make, who consider Miosha Peshkov as a harmonic personality. Gorky shows that the personality cannot be a harmonic personality without the realistic world outlook.
Keywords: -